Pengaruh Penggunaan Aplikasi Wordwall dalam Meningkatkan Kemampuan Mengenal Huruf Anak Usia Dini - Yoseph Marianus S. R. L. Kerore; Vanida Mundiarti; Theodorina N. Seran; Gokma Nafita Tampubolon; Credo G. Betty (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
The ability to recognize letters is an important indicator in assessing the language development of early childhood as a basis for readiness to read and write. However, in learning practices, there are still limitations in the use of varied and interesting media, so that children's letter recognition abilities have not developed optimally. This study aims to determine the effect of using a wordwall application in improving letter recognition abilities in early childhood at PAUD ST. Alexander Oelnitep. This study used a quantitative pre-experimental approach with a one-group pretest-posttest design. The research sample consisted of 11 children aged 5-6 years, consisting of 2 boys and 9 girls. The study was conducted in two stages, namely a pretest aimed at determining children's initial ability in recognizing letters before using the wordwall application, and a posttest to measure abilities after being given treatment. The research instrument was first tested for feasibility and readability. Data analysis used was a hypothesis test using the Wilcoxon test. The results showed an increase in the average value after being given treatment. Based on the results of the Wilcoxon test, it shows that the mean pretest = 00 while the mean posttest = 6.00 and the results of the statistical test output, the asymp. Sig (2-tailed) value is 0.003. These results indicate that the hypothesis Ho which states that the use of wordwall applications has no effect in improving the ability of early childhood to recognize letters in PAUD ST. Alexander Oelnitep is rejected, while the alternative hypothesis Ha which states that the use of wordwall applications has an effect in improving the ability of early childhood to recognize letters in PAUD ST. Alexander Oelnitep is accepted. Overall, the use of wordwall application media has been proven to have an effect in improving the ability to recognize letters in early childhood.